2013
DOI: 10.1021/jo400861j
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Absolute Configuration, and Conformational Study of 12-Membered Macrolides from the Fungus Dendrodochium sp. Associated with the Sea Cucumber Holothuria nobilis Selenka

Abstract: Dendrodolides A-M (1-13), 13 new 12-membered macrolides, were isolated from Dendrodochium sp., a fungus associated with the sea cucumber Holothuria nobilis Selenka, which was collected from the South China Sea. The structures of the dendrodolides were elucidated by means of detailed spectroscopic analysis and X-ray single-crystal diffraction. The absolute configurations were assigned using the modified Mosher method, exciton-coupled circular dichroism (ECCD), electronic solution and solid-state circular dichro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 84 publications
6
143
0
1
Order By: Relevance
“…These conformers were reoptimized at two different DFT levels, namely B3LYP/6-31G(d) in vacuo and B97D/TZVP [1617] with a Polarizable Continuum Model (PCM) for MeCN [18]. The B3LYP optimization yielded 10 low-energy conformers above 2% Boltzmann population, while the number of low-energy conformers was 14 at the applied B97D level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These conformers were reoptimized at two different DFT levels, namely B3LYP/6-31G(d) in vacuo and B97D/TZVP [1617] with a Polarizable Continuum Model (PCM) for MeCN [18]. The B3LYP optimization yielded 10 low-energy conformers above 2% Boltzmann population, while the number of low-energy conformers was 14 at the applied B97D level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…38 Geometry reoptimizations were carried out at the B3LYP/6-31G(d) level in vacuo, the B3LYP/6-31+G(d,p) level in vacuo, the B97D/TZVP 20,21 and the CAMB3LYP/ TZVP 22,23 levels with the PCM solvent model for MeCN or MeOH. TDDFT ECD calculations and OR calculations were run with various functionals (B3LYP, BH&HLYP, CAM-B3LYP, PBE0) and the TZVP basis set as implemented in the Gaussian 09 package with the same or no solvent model as in the preceding DFT optimization step.…”
Section: Computational Sectionmentioning
confidence: 99%
“…10 In a program designed to identify antimalarial drug leads, it was found that psammaplysins F−H exhibited strong antimalarial activity. 8,9 We recently reported the isolation of psammaplysins K−W, together with 19-hydroxyplammaplysins E, P, Q, S, T, U, and W, from an extract of the Balinese sponge Aplysinella strongylata (order Verongida, family Aplysinellidae), with five of these new psammaplysins showing variation in the structural motif attached to C-16 of the aromatic ring, while the remaining compounds contained fatty acid side chains; 19-hydroxypsammaplysin E showed potent antimalarial activity. 11 The relative configuration of psammaplysin A (1) was first determined as (6S*,7S*) in 1985 by single-crystal X-ray crystallographic analysis of its diacetyl derivative (2).…”
mentioning
confidence: 99%